2015
DOI: 10.5897/err2014.1975
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity analysis in academic achievement at higher education preparatory schools: Case of South Wollo, Ethiopia

Abstract: Gender is among the determinant factors affecting students' academic achievement. This paper tried to investigate the impact of gender on academic performance of preparatory secondary school students based on 2014 EHEECE result. Ex post facto research design was used. To that end, data were collected from 3243 students from eight purposively selected schools. The analysis has been undertaken quantitatively using independent samples t-test, one sample t-test, Pearson correlation coefficient, Chi-square test, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…They attributed this phenomenon in line with the view that male students spend so much time on social media while the female students who are not allowed access to social media, studied harder. In disagreement with the above view, Amogne [39] found that there is a statistically significant difference between male and female students' achievement in favor of the male students. The author reported that male students have higher mean achievement in Accounting than female students.…”
Section: Influence Of Gender On Student's Social Media Usage and Student's Academic Achievementmentioning
confidence: 83%
See 1 more Smart Citation
“…They attributed this phenomenon in line with the view that male students spend so much time on social media while the female students who are not allowed access to social media, studied harder. In disagreement with the above view, Amogne [39] found that there is a statistically significant difference between male and female students' achievement in favor of the male students. The author reported that male students have higher mean achievement in Accounting than female students.…”
Section: Influence Of Gender On Student's Social Media Usage and Student's Academic Achievementmentioning
confidence: 83%
“…On the other hand, researches among Chinese and British students have reported the males engage themselves in using social media more than the females as they appear to be more skilled technologically than the females [38]. It was reported by [39] that a significant difference exists between the achievement of male and female students with the male students having a better achievement than the females. In agreement with this view, Hasan and Khan [40] asserted that there is a significant influence of gender on students` academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Isaac's (2014) study also found that drought-related factors affect pupils' participation in school due to the reduced source of income of parents whose businesses depended heavily on water. Similarly, findings exist that drought-related matters affect the learners' tendencies to continue in school, perform maximally as anticipated, participate in school activities, and develop the right skills, especially in developing countries, where agriculture is the mainstay of their economies (Amogne & Tessema, 2017;Doherty & Clayton, 2011;Nkeiruka, 2014).…”
Section: Studies On Persistence Droughtmentioning
confidence: 99%
“…They reported that a smaller number of female students managed to enter the university indicating the less competitiveness of female students. Tasisa and Tafesse (2013) concluded that there are significant differences between male and female students in academic achievement in both Ethiopian General Secondary Education Certificate Examination (EGSECE) and college cumulative GPA. Empirical findings supported better performance of male students than females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A discrete-time Markov chain model has been employed to derive the results. Eshetu (2015) investigated the impact of gender and age on academic performance. This study has important bearing since the age was found inversely impacting academic results, and gender caused a differential in degree achievement.…”
Section: Literature Reviewmentioning
confidence: 99%